On-farm management of rice genetic diversity:understanding farmers' knowledge on rice ecosystems and varietal deployment - Rana, R.B.=700 1 Garforth, C.J.; Sthapit, B.R.
(Es, En, Pt)
ilus., 11 ref.
Keywords: ORYZA SATIVA; VARIACION GENETICA; ECOSISTEMA; VARIEDADES; ITALIA; ARROZ; NOTICIARIO DE RECURSOS FITOGENETICOS